Artist's Statement: Healthy Soil in Bloom - Mary Ellenberger (Interdisciplinary Journal of Partnership Studies)
Artist’s Statement for the cover art of the Interdisciplinary Journal of Partnership Studies, Volume 12, Issue 1: Healthy Soil in Bloom, Digital Photo Collage.